IDENTITAS ACEH DAN INDONESIA; : Melihat Aceh dan Indonesia Dalam Perspektif Sejarah - Irwan Adaby (AT-TANZIR: JURNAL ILMIAH PRODI KOMUNIKASI PENYIARAN ISLAM, 2017)
The tempesteous relationship between Aceh and Indonesia made many experts frequently connect among Aceh and Indonesia Identities. It is impressed that the allignment between both identities are coercion and only delusion of Aceh people who are considered lost in their aceh identities. That matter is considered to have been engineered by Indonesia to establish sosial and cultural hegemony of javanesse in Indonesia Republic. Beside, many people do not have knowladge about the the beginning process of the Aceh becoming part of indonesia and how the dynamic and transformation process of both identity which have been united in Indonesia. This research reviewed the transformation both identity in historical perspective based on the facts and political communication from both identity.